Molecular Detection of Multi-drug Resistant Acinetobacter baumannii from Patients Wounds - Amina N. Al-Thwani (Journal of Global Pharma Technology, 2020)
150 swabs were collected from patient's wounds and hospital units, population of this study included both genders with different ages in AL-Imamein AL-Kadhimein Medical City in Baghdad. The collected swabs were cultured using appropriate media and tested biochemically in order to find out the profile of bacteria that colonize patient's wounds and hospital units. The results of culture revealed that, the most common isolated bacteria were, Staphylococcus aureus followed by Pseudomonas aeruginosa and A.baumannii. The isolates of A. baumannii was tested for antibiotic susceptibility, the results showed that, clinical and environmental isolates were (100%) resist to Ceftriaxone, Ceftazidime Ampicillin–Sulbactam, and Cefepime. Metallo Beta Lactamase (MBL) genes as bla IMP gene and bla VIM were detected by Molecular method (PCR) in 12 clinical and environmental isolates of A.baumannii. The result revealed that among all isolates (12) only bla IMP gene was detected in 4 isolates while the reminder isolates (8) of A.baumannii have no amplified bands for neither bla VIM nor bla IMP. It was concluded that, A.baumannii responsible for many nosocomial infections, and these bacteria were high resistant to different types of antibiotics.